2017
DOI: 10.1080/13685538.2017.1303827
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative sexual status of Japanese localized prostate cancer patients: comparison of sexual activity and EPIC scores

Abstract: The present survey showed that more than quarter of preoperative middle-aged Japanese prostate cancer patients surveyed had actual sexual activity, though not within the preceding 4 weeks. To precisely evaluate sexual function of middle-aged Japanese patients, it is necessary to consider actual sexual activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A questionnaire surveying sexual intercourse over a certain period of time did not indicate accurate SF, at least for elderly Japanese patients with PCa. Our present study showed a significant difference in the frequency of sexual intercourse and sexual activity, and the fact that the evaluation of SF after RP includes a question about sexual activity was considered important [20].…”
Section: Discussionmentioning
confidence: 48%
“…A questionnaire surveying sexual intercourse over a certain period of time did not indicate accurate SF, at least for elderly Japanese patients with PCa. Our present study showed a significant difference in the frequency of sexual intercourse and sexual activity, and the fact that the evaluation of SF after RP includes a question about sexual activity was considered important [20].…”
Section: Discussionmentioning
confidence: 48%
“…Sexual activity and sexual function have investigated via the Expanded Prostate Cancer Index Composite (EPIC) and an original self-reported questionnaire. In the same survey showed that more than quarter of preoperative middle-aged Japanese prostate cancer patients surveyed had actual sexual activity, though not within the preceding 4 weeks [28]. Benign prostatic hyperplasia (BPH) is a common age for men.…”
Section: Discussionmentioning
confidence: 99%
“…2 On the other hand, it has been reported that fewer middleaged Japanese men have regular sexual intercourse than men of other races or cultures. Taniguchi et al 3 reported that about a quarter of middle-aged men who underwent radical prostatectomy actually had sexual intercourse. On the other hand, about three quarters of current prostate cancer patients who undergo total prostatectomy do not have regular sexual intercourse.…”
Section: Editorial Commentmentioning
confidence: 99%
“…On the other hand, it has been reported that fewer middle‐aged Japanese men have regular sexual intercourse than men of other races or cultures. Taniguchi et al 3 . reported that about a quarter of middle‐aged men who underwent radical prostatectomy actually had sexual intercourse.…”
mentioning
confidence: 99%